Pedagogia de projetos em foco: abordagem interdisciplinar na educação fundamental - Silva, Rafaela Andurand e (Brasil, 2023)
In this study entitled “Pedagogy of projects in focus: an interdisciplinary approach in fundamental education” we made efforts to carry out a conceptual, historical and reflective deepening of the theme, with the concern of contextualizing the two approaches, making the proper articulation with the process of theoretical formation and methodological experience experienced in the graduation in pedagogy. The study was structured around the following objectives: to conceptualize interdisciplinarity in the educational field; Know the theoretical and methodological foundations of Project Pedagogy; Reflect on the existing pedagogical gaps in the Initial Formation of the future teacher with regard to the assimilation of the principles of the interdisciplinary approach applied to the formation of the child. In our methodological course of exploratory research, we carried out a survey of three course conclusion works and three dissertations related to the theme. We also carried out a documentary consultation with the Amazonian Curriculum Reference of the Municipal Secretary of Education for the Initial Years, completing with direct observations in a municipal school during the period of mandatory internship in Elementary School I. We found that the adoption of project pedagogy from the perspective of an interdisciplinary approach of the curriculum in action in the early years, it is still something to be instituted, although it is regulated in the municipal curriculum proposal; and initial training at the university needs more inclusion in the components of the course's curricular matrix, it is clear that gaps in theoretical consistency persist due to the conceptual mastery of approaches. So, the debate continues. Discussions on the theme become increasingly important, since they need to be effectively used in public schools, strengthening and promoting the process of meaningful formation of children in the early years of elementary school.